The effectiveness of neuromuscular training in preventing sports injuries of different genders, body parts, and types in adolescents: a systematic review of meta-analysis - Sun, Liang; Luo, Lanfang; Yang, Yi; Luo, Jiong (Quality in Sport, 2024)
Objective: Neuromuscular training is a relatively new comprehensive rehabilitation treatment method in recent years. Although its preventive effect on adolescent sports injuries is indisputable, its specific effects on gender, injury site, and type are still poorly understood. This study evaluated the clinical efficacy of neuromuscular training on adolescents of different genders, injury sites, and types through systematic meta-analysis. Method: A comprehensive search was conducted on clinical randomized controlled trials related to the prevention of adolescent sports injuries through neuromuscular training in databases such as PubMed, Web of Science, EBSCO, and Scopus. The databases were established until May 2024. The neuromuscular training group (experimental group) used neuromuscular training or neuromuscular training as the main intervention method; The control group is either a blank group or a routine exercise group, without paying special attention to neuromuscular control. Outcome measures include any form of muscle, ligament, or bone injury, including acute or chronic injury data. The quality of the included literature was determined using the Cochrane bias risk assessment tool and the physical therapy evidence database scale, and statistical analysis was conducted using RevMan 5.4 and Stata 16.0 software.This study is registered with the International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY), INPLASY2024110054. Result: A total of 32 clinical randomized controlled trials were included, with a sample size of 34581 cases. The meta-analysis results showed that: 1. The overall effect of neuromuscular training: the experimental group was better than the control group, with a combined IRR of 0.67 (95% CI2 0.57-0.79); Z = 4.78;P < 0.00001). The male group had a higher risk of loss compared to females in the experiment; 2. Upper limb motor injury: combined IRR of 0.73 (95% CI2 0.59-0.9); Z = 3.12;P =0.002). The male group had a lower risk of injury compared to females in the experiment. 3. Lower limb motor injury: combined IRR of 0.66 (95% CI2 0.56-0.77); Z = 5.12;P< 0.00001). The male group had a higher risk of loss compared to the female group in the experiment. 4. Knee movement injury: combined IRR of 0.73 (95% CI2 0.63-0.84); Z = 4.44;P< 0.00001). The female group had a higher risk of loss compared to the male group in the experiment. 5. Ankle sports injury: combined IRR of 0.54 (95% CI2 0.40-0.74); Z = 3.90;P< 0.00001). The male group had a higher risk of loss compared to females in the experiment. 6. Acute sports injury: The combined IRR is 0.60 (95% CI2 0.49-0.74); Z = 4.84;P< 0.00001), The male group had a similar reduced risk of loss compared to females in the experiment. 7. Chronic sports injury: The combined IRR was 0.72 (95% CI2 0.52-0.98; Z=2.07; P=0.04), and the female group had a higher risk of loss compared to males in the trial. Conclusion: Neuromuscular training has significant effects in preventing upper and lower limbs, knees, ankles, and acute and chronic sports injuries of different genders. Research has shown that neuromuscular training has similar effects on different genders, effectively reducing the burden of public health and promoting participation in sports activities. However, more high-quality randomized controlled trials are still needed to further validate these findings.